An overview of modern metal additive manufacturing technology. (December 2022) - Armstrong, Mark; Mehrabi, Hamid; Naveed, Nida
Abstract: There has been significant development in metal additive manufacturing (MAM) technology over the past few decades, and considerable progress has been made in understanding how various processes and their parameters influence the properties of printed metallic parts. Despite this, the knowledge concerning its characteristics has been dispersed across a variety of publications and sources, making it difficult to gain a comprehensive understanding of the entire field, especially for businesses interested in additive manufacturing (AM). In order to bridge this gap, periodic reviews encompassing state-of-the-art as the whole are necessary. Therefore, this article provides a comprehensive overview of the essential features of MAM techniques based on the most recent scientific knowledge. It explores emerging research on four of the most significant technologies, including material extrusion (ME), binder jetting (BJ), powder bed fusion (PBF), and directed energy deposition (DED). As well as providing an outline of fundamental process characteristics, ongoing efforts to optimize them and current challenges, it also highlights gaps in understanding and future research and development needs. A significant feature of this review is the provision of substantial documentation regarding the mechanical properties of materials processed by a variety of commercial systems, including a variety of novel hybrid additive manufacturing (HAM) machines. This is accompanied by an investigation into the most recent works done to characterize the environmental impact along with a conceptual framework for improving the energy efficiency (EE) of the manufacturing process. As a result of reporting on both the characteristics of several MAM processes along with their sustainability features in one integrated article, it is anticipated that this information will serve as a valuable resource for both the academic and manufacturing communities to better appreciate and understand what differentiates MAM from traditional manufacturing (TM) processes, thus facilitating its future advancement and adoption.